Public Speaking Training For Students of International Class Program State Islamic University Walisongo to Improve The Ability of Maharah Kalam - Inayah, Inayah; Asikin, Alis; Rokhani, Rokhani; Mustavid, Alvian Varihul; Abdillah, Dzaky Hamid (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Productive competence in language are important things in upgrading the quality of language and developing it in terms of skills. Based on interview, the students in the International Class Program (ICP) at State Islamic University of Walisongo have not attained proficiency in speaking and they need special training related to that skill. The ICP consists of 3 departments: the Department of Arabic Teaching, the Department of English Teaching, and the Department of Islamic Sciences Teaching for the fifth and third levels, with total of 114 students. Public Speaking Training passed on 3 waves of the subject,1.Public Speaking Skills and Tips, 2.Overcoming fear of Public Speaking, 3.Improve your public speaking. This research is qualitative descriptive research, in terms of public speaking training for students in ICP. The data collection method used is observation, documentation and testing with the YouTube video tool. Analyzing data with inductive qualitative analysis from Miles and Huberman's theory depending on the continuous steps are data collection, data reduction, presentation, conclusion drawing or verification. The objectives of the research are: A- How to implement public speaking training for students in the ICP? B- How is the speaking skill of students through the final exam after public speaking training? The result of the research is that the application of public speaking training in this university through experts in three classes, and that public speaking training has an important function to upgrade the competencies in the speaking skill of students in ICP at State Islamic University of Walisongo, Semarang